Determination of potential groundwater sources using electrical resistivity imaging (ERI) in Lojing, Gua Musang. Issue 1 (August 2021) - Sulaiman, N; Saliman, N S M; Sulaiman, N
Abstract: The study area is located at the sub-district of Lojing, Gua Musang, Kelantan. The dimension of the study area is approximately 25km2. This study aims to determine the possibility of groundwater existence using Electrical Resistivity Imaging (ERI) method. The lithology of the study area is a metamorphic rock which is schist and the parent rock for schist is a sedimentary rock. Schist has a characteristic that not suitable for groundwater accumulation between grains, therefore the groundwater may exist within the fractured zones. In Kelantan, it used both groundwater and surface water treatment as their main resources for daily uses. However, continuous extraction of groundwater can cause depletion and continuous contamination of the river and reduces the quality of water treatment. Therefore, new sources of groundwater are needed to support the water storage. The study area has a high potential of groundwater located in the subsurface. ERI results show that the subsurface consists of low resistivity material such as sedimentary rocks that can store groundwater in a large volume. Therefore, the study area is highly potential as a zone for groundwater accumulation.